2020
DOI: 10.1038/s41419-020-03071-y
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine METTL3 promotes cervical cancer tumorigenesis and Warburg effect through YTHDF1/HK2 modification

Abstract: N6-methyladenosine (m6A) serves as the most common and conserved internal transcriptional modification. However, the roles of m6A on cervical cancer (CC) tumorigenesis are still unclear. Here, results indicated that METTL3 was significantly upregulated in CC tissue and cells, which was closely correlated with the lymph node metastasis and poor prognosis of CC patients. MeRIP-Seq analysis revealed the m6A profiles in CC cells. Functionally, METTL3 promoted the proliferation and Warburg effect (aerobic glycolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(201 citation statements)
references
References 29 publications
6
194
1
Order By: Relevance
“…21 Thus, an increasing number of studies on cancer metabolism are examining the regulation of HK2 expression as a promising anticancer strategy. 10,21,22 HK2 contributes to increasing the glycolytic capacity and proliferation of GBM cells. 23 Human ATP citrate lyase (ACLY) catalyzes the ATP-dependent synthesis of oxaloacetate and acetyl-coenzyme A (acetyl-CoA) from citrate and coenzyme A (CoA), which is a key enzyme in lipid synthesis.…”
Section: Key Enzymes In Glioma Glycolipid Metabolismmentioning
confidence: 99%
“…21 Thus, an increasing number of studies on cancer metabolism are examining the regulation of HK2 expression as a promising anticancer strategy. 10,21,22 HK2 contributes to increasing the glycolytic capacity and proliferation of GBM cells. 23 Human ATP citrate lyase (ACLY) catalyzes the ATP-dependent synthesis of oxaloacetate and acetyl-coenzyme A (acetyl-CoA) from citrate and coenzyme A (CoA), which is a key enzyme in lipid synthesis.…”
Section: Key Enzymes In Glioma Glycolipid Metabolismmentioning
confidence: 99%
“…It has been reported that HPVs generated circRNAs encompassing the E7 oncogene (circE7), which was subjected to m 6 A modification, and promoted the proliferation of tumor cells ( 39 ). METTL3 promoted the stability of H2K through m 6 A modification, thereby promoting Warburg effect and the proliferation of cervical cancer cells ( 40 ). Here, we found that YTHDF1 is up-regulated in cervical cancer tissues and predicts the poor clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…RNA expression levels were measured using quantitative real-time polymerase chain reaction (qRT-PCR) as previously described 26 . Glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ) was used as an endogenous control and Hut78 cells for calibration 29 31 . The primers (Supplementary Table 2 ) were provided by Biosune Biotechnology Company (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%